Trabajo infantil, migración y derechos humanos en Ecuador. - Yacelga Andrade, Flora Ricardina. (2019)
Child labor and immigration are phenomena of worldwide incidence that lead children to be in a situation of double vulnerability due to the violations of rights that it frequently involves. Therefore, state, family and social protection is essential, which promotes, guarantees and protect the development of children; and, in this way, the eradication of child labor becomes a priority element within Ecuadorian laws. National and international regulations and public politics are favorable tools for the integral protection of their rights. Between 2015 and 2017, Ecuador became involved in a migratory process, consistent with the Venezuelan diaspora, and was not prepared to face it adequately. Therefore, it considers this as a security problem and resorts to measures contrary to its quality as a guarantee state, compliance by the Ecuadorian State with the commitments made at the international level regarding the guarantee and protection of the rights of Venezuelan children in their territory with respect to child labor is analyzed.